Comparative Assessment of Seasonal Variation in Size-Segregated Particulate Matters around Urban Drains - Jamloki, Asha; Ranjan, Anuj; Chauhan, Abhishek; Tyagi, S.K.; Jindal, Tanu (Asian Journal of Chemistry, 2022)
The rapidly growing urbanization has resulted in increased environmental pollution and degradation that has equally affected the quality of air and wastewater. Urban drains that carry wastewater from households and industries are also carrying loads of pollutants. The current study was conducted to compare the trend in the concentration of particulate matter (PM) in the air, across the seasons near the urban drains in Delhi, a metropolitan city. The air samples were taken from Najafgarh drain, which is the biggest drain of Delhi city and has a contribution of about 60% of the total wastewater released from Delhi city into river Yamuna. The Indian Standard method IS 5182 Part 24:2019 was used for PM2.5 & IS 5182 Part 23:2006 was used for PM10 monitoring and analysis. The results of the analysis showed that the variation in particulate matter (PM) is observed with changes in relative humidity and with seasonal changes. The variation in PM2.5 levels was seen in a range of 55.30-118.42 μg/m3 from June 2020 to February 2021 & in PM10 levels were seen in the range of 77.54-261.99 μg/m3 during June 2020 to February 2021 for location L1. The variation in PM2.5 levels was seen in a range of 23.84-76.94 μg/m3 from June 2020 to February 2021 & in PM10 levels were seen in the range of 42.06-149.48 μg/m3 during June 2020 to February 2021 for location L2. Few studies have shown that contaminants can enter into the fresh air from the municipal wastewaters and open drains.